Jak-TGFβ cross-talk links transient adipose tissue inflammation to beige adipogenesis - Babaei, Rohollah; Schuster, Maximilian; Meln, Irina; Lerch, Sarah; Ghandour, Rayane A.; Pisani, Didier F.; Bayındır-Buchhalter, İrem; Marx, Julia; Wu, Shuang; Schoiswohl, Gabriele; Billeter, Adrian; Krunic, Damir; et al. (Science signaling, 2018)
Committing progenitors to adipogenesis - Promoting the “browning” of white fat has been proposed as a strategy to combat obesity. Beige adipocytes, which are intermediate between fat-storing white adipocytes and thermogenic brown adipocytes, can emerge from the differentiation of adipocyte progenitors in adipose tissue in response to β3-adrenergic stimulation. Using primary human and mouse cells and ex vivo mouse models, Babaei et al. (see also the Focus by Sun et al.) found that the Jak family of kinases promoted the commitment of adipocyte progenitors to beige adipogenesis. Through the downstream transcription factor Stat3, Jak inhibited TGFβ signaling and prevented adipocyte progenitors from differentiating into smooth muscle cells. β3-Adrenergic stimulation of lipolysis, which transiently triggers inflammation, induced the production of the cytokines IL-6 and IL-11, which activated the Jak/Stat3 pathway. These results delineate a pathway that is activated by transient inflammation in adipose tissue that steers adipocyte progenitors toward differentiation into a thermogenically active form of fat. - The transient activation of inflammatory networks is required for adipose tissue remodeling including the “browning” of white fat in response to stimuli such as β3-adrenergic receptor activation. In this process, white adipose tissue acquires thermogenic characteristics through the recruitment of so-called beige adipocytes. We investigated the downstream signaling pathways impinging on adipocyte progenitors that promote de novo formation of adipocytes. We showed that the Jak family of kinases controlled TGFβ signaling in the adipose tissue microenvironment through Stat3 and thereby adipogenic commitment, a function that was required for beige adipocyte differentiation of murine and human progenitors. Jak/Stat3 inhibited TGFβ signaling to the transcription factors Srf and Smad3 by repressing local Tgfb3 and Tgfb1 expression before the core transcriptional adipogenic cascade was activated. This pathway cross-talk was triggered in stromal cells by ATGL-dependent adipocyte lipolysis and a transient wave of IL-6 family cytokines at the onset of adipose tissue remodeling induced by β3-adrenergic receptor stimulation. Our results provide insight into the activation of adipocyte progenitors and are relevant for the therapeutic targeting of adipose tissue inflammatory pathways. - Transient inflammation in adipose tissue triggers Jak-TGFβ signaling to promote beige adipocyte differentiation. - Transient inflammation in adipose tissue triggers Jak-TGFβ signaling to promote beige adipocyte differentiation.